TRANSLATION ANALYSIS ON TUTORIAL VIDEO OF MOBILE LEGEND FROM ENGLISH TO INDONESIA AT YOUTUBE CHANNEL - Raka Rizki Ramadhan; Rahmanti Asmarani (Jurnal CULTURE (Culture, Language, and Literature Review), 2019)
This paper has three objectives: To describe the strategies used by the content creator, to explain about the tutorial of the heroes, to explain the strategy mostly applied in the tutorial videos of the heroes and to analyze the accuracy of the translation. The data is Mobile Legends’ video tutorial. After analyzing the data, there are 54 translation strategies in the data. The researchers analyze the data by using Malone’s framework (1998) about translation strategy. There are 5 strategies found in the data. The strategy most applied in the data is divergence with 29 times or 55.5%. It happened because mostly the caption translated by using dictionary meaning. Here, the translation applies the divergence since the meaning of the word range is based on dictionary. The accurate level becomes the highest level with average of 50 data or 93.6 %. It happens because most of the raters agree that the translator can deliver the meaning and the context well. The second rank is the inaccurate level with 3 data or 5.5%. Keywords: accuracy, divergence, mobile legend, strategies, tutorial